Bangladesh - Development Policy Review : Impressive Achievements but Continuing Challenges - World Bank (Washington, DC, 2013)
Bangladesh has marked considerable progress since independence in 1971 despite its dire initial conditions. Real per capita income is about 60percent higher now than in 1971. The share of population in poverty currently stands at about 50 percent, compared with over 70 percent in the early 1970s. Even more impressive has been the progress in improving the social and human dimensions of poverty. Bangladesh's faster gains in human development than in income growth result from public policies that have complemented the remarkable energy at the grassroots level. This energy was effectively channeled by the country's nongovernmental organizations and community-based organizations, many of which are world leaders in their innovative ideas and operational methods. Many challenges remain to be addressed, however, especially in the area of institutions. Remaining gaps in policies and weak institutions have impeded a faster pace of development. Inadequate improvement in governance has particularly constrained the investment climate and greatly diminished the state's ability to deliver basic social services, especially to the poor. The situation requires urgent action on the bold reform agenda adopted by the new government in the context of its Interim Poverty Reduction Strategy Paper (I-PRSP) in 2003. The authorities need to accelerate the pace of structural reforms-particularly in the areas of infrastructure (physical and financial), macroeconomic management, and overall governance-to improve the investment climate and strengthen social inclusion and participation. Unless this is done, Bangladesh will not be able to achieve the goals laid down in the I-PRSP; indeed, the gains already achieved risk being eroded.